Rapid self-healing hydrogels - Phadke, Ameya; Zhang, Chao; Arman, Bedri; Hsu, Cheng-Chih; Mashelkar, Raghunath Anant; Lele, Ashish K.; Tauber, Michael J.; Arya, Gaurav; Varghese, Shyni (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Synthetic materials that are capable of autonomous healing upon damage are being developed at a rapid pace because of their many potential applications. Despite these advancements, achieving self-healing in permanently cross-linked hydrogels has remained elusive because of the presence of water and irreversible cross-links. Here, we demonstrate that permanently cross-linked hydrogels can be engineered to exhibit self-healing in an aqueous environment. We achieve this feature by arming the hydrogel network with flexible-pendant side chains carrying an optimal balance of hydrophilic and hydrophobic moieties that allows the side chains to mediate hydrogen bonds across the hydrogel interfaces with minimal steric hindrance and hydrophobic collapse. The self-healing reported here is rapid, occurring within seconds of the insertion of a crack into the hydrogel or juxtaposition of two separate hydrogel pieces. The healing is reversible and can be switched on and off via changes in pH, allowing external control over the healing process. Moreover, the hydrogels can sustain multiple cycles of healing and separation without compromising their mechanical properties and healing kinetics. Beyond revealing how secondary interactions could be harnessed to introduce new functions to chemically crosslinked polymeric systems, we also demonstrate various potential applications of such easy-to-synthesize, smart, self-healing hydrogels.
Keywords: adhesives; biomimetic materials; Hydrophobicity; molecular dynamics; smart materials